Mitigating Culture Shock Through Intercultural Communication: A Case Study of Expatriates in South Jakarta - Lena, Pratika Martha; Wahyuningtias, Dinda Dwimanda; Maryami (Yayasan Ilomata, 2025)
This study investigates how expatriates in South Jakarta employ intercultural communication strategies to mitigate culture shock and adapt to a new cultural environment. As global mobility increases, understanding the psychological and social challenges faced by expatriates in multicultural urban settings becomes crucial. Using a qualitative case study approach, in-depth interviews were conducted with seven expatriates of diverse cultural backgrounds. The findings reveal that expatriates experience significant culture shock in the form of language barriers, unfamiliar social norms, and emotional disorientation during their initial adaptation phase. To address these challenges, they employ various strategies such as learning the local language, adjusting communication styles, building social support networks, and participating in community activities. These strategies facilitate gradual adaptation and foster intercultural competence, leading to a sense of belonging and bicultural identity. The study highlights that cultural adaptation is a reciprocal process, where both expatriates and local communities engage in mutual exchange and learning. The results provide practical insights for organizations and policymakers to support expatriate adjustment and promote inclusive multicultural environments.